2010
DOI: 10.1016/j.drugalcdep.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent outpatient treatment and continuing care: Main findings from a randomized clinical trial☆

Abstract: This study evaluated the effectiveness and cost-effectiveness of two types of outpatient treatment with and without Assertive Continuing Care (ACC) for 320 adolescents with substance use disorders. Study participants were randomly assigned to one of four conditions: (a) Chestnut’s Bloomington Outpatient Treatment (CBOP) without ACC; (b) CBOP with ACC; (c) Motivational Enhancement Therapy/Cognitive Behavior Therapy-7 session model (MET/CBT7) without ACC; and (d) MET/CBT7 with ACC. All study conditions attained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(128 citation statements)
references
References 36 publications
3
124
1
Order By: Relevance
“…Most (56%) had one or more co-occurring mental health disorders. There were no statistically significant findings for the effectiveness of ACC 71 .…”
Section: Research On Continuing Care For Adolescents After Outpatientmentioning
confidence: 78%
“…Most (56%) had one or more co-occurring mental health disorders. There were no statistically significant findings for the effectiveness of ACC 71 .…”
Section: Research On Continuing Care For Adolescents After Outpatientmentioning
confidence: 78%
“…H. Godley et al (2010) found that the use of ACA was related to an increase in the percentage of abstinent days compared to treatment models that did not use ACC. The participants were recruited through various outreach efforts.…”
Section: Program Descriptionmentioning
confidence: 97%
“…Adolescent Community Reinforcement Approach (a-CRA) is a comprehensive substance use treatment intervention that involves both the adolescent and their families in the sessions. It seeks to increase the family, social, and educational/vocational reinforcers of an adolescent to support recovery and to encourage prosocial activities (44). Assertive Continuing Care (ACC), a home-based intervention, combines a-CRA and case management for a duration of 12-14 weeks, to work with adolescents discharged from residential or outpatient treatment to help maintain the progress achieved during active treatment.…”
Section: Functional Family Therapy (Fft) Is Based Onmentioning
confidence: 99%